Effects of preoperative psoas muscle index and body mass index on postoperative outcomes after video‐assisted esophagectomy for esophageal cancer. Issue 4 (23rd March 2021) - Uemura, Shion; Shichinohe, Toshiaki; Kurashima, Yo; Ebihara, Yuma; Murakami, Soichi; Hirano, Satoshi
Abstract: Introduction: Preoperative psoas muscle index (PMI) and body mass index (BMI) are relevant to postoperative outcomes. We investigated the associations of PMI, BMI, and preoperative nutritional and muscular score with postoperative outcomes in patients with esophageal cancer who underwent video‐assisted surgery. Methods: We examined 150 patients (124 men, 26 women) who underwent video‐assisted esophagectomy from February 2002 to March 2016. We used the Clavien‐Dindo (CD) classification to analyze postoperative complications. Because skeletal muscle volume differs significantly between male and female patients, all analyses were performed separately. In male patients, we used the following cut‐off values to categorize patients into three groups: PMI = 600 mm 2 /m 2, BMI = 18.5 kg/m 2, and preoperative nutritional and muscular (PNM) scores 0 to 2. Results: Two patients were converted to open thoracotomy. Among male patients, PMI and PNM scores were significant risk factors for complications. Among male patients, in the high PMI group, the number of CD ≥ IIIa complications was significantly lower. In the PNM score 0 group (both PMI and BMI values exceeded the cut‐off values), the number of complications was significantly lower. In both genders, PMI and BMI were not significantly associated with survival. Conclusions: PMI and PNM scores can be useful for predicting postoperative outcomes in male patients with esophageal cancer having undergone video‐assisted surgery.